Presidencialismo estadual em São Paulo: o que une os partidos na coalizão - Massonetto, Ana Paula (2014)
The central theme of this thesis is inserted in the literature which investigates the logic of power relations between the executive and legislative powers in the sub-national sphere, and in particular, on how the paradox of governability is solved in Brazilian states. Seeking a better understanding on how parties unite in coalitions, the thesis analyses the assembly and the nature of government coalitions (Cabinet formations), investigating, in particular, the weight and role of cabinets in the formation and maintenance of executive support by the legislative chamber of the state of São Paulo, from 1995 to 2010. The empirical study finds that differently from the federal sphere, the formation of São Paulo’s cabinets aim mostly at electoral strategies and that the governors’ formed and maintained coalitions are not totally explained by the government focused coalitions. Government coalitions essentially represent minor parties, and generally only allieds are appointed as secretaries of state, not proportionally to the legislative support, with the majority of roles being offered to the governor’s party. The formation and management of legislative coalitions are accomplished through the offer of coalition tools and pork barrels, such as 2nd and 3rd tier appointments, monetary transfers, and investments in legislative members’ electoral districts. The legislative members’ governist behavior is justified by the lack of alternative for political survival, derived from the current conditions, which include restrictions or lack of institutional incentives, such as: Diminished state competencies, major matters being exclusive to the executive power, Legistative carrier strategy derived from the proportional open-list electoral system, among others. The thesis contributes to the stream of empirical studies about coalition presidentialism, bringing elements on the cabinet formation and long term coalition management.